Sexual harassment in context of Malaysia - Ali Hassan Humaid Alhosani, Adnan; Ismail, Fadillah; Johar, Siti Sarawati; Md Yusoff, Rosman (Penerbit UTHM, 2020)
Sexual harassment is a form of sex discrimination or unwelcome sexual action includes verbal or physical touch that can affect the individual’s employment, work performance and others including physical and mental health. Sexual harassment may occur in many condition or situation such as between opposite gender or with the same gender. The victim may be the superior, co-worker, an agent or to a non-employee (U. S. E. E. O. Commission, n.d.). Sexual harassment also not an action with interactivity, friendship or teasing that is mutually agreed (V. E. O. & H. R. Commission, n.d.). However, there are two types of sexual harassment, “quid pro quo” (this for that) and hostile environment. For “quid pro quo”, this occur when it is stated or implied that an individual must agree to conduct a sexual nature in order to get promotion. Other that, hostile environment occur when there is unwelcome action of a sexual nature create frighten, abusive working or threatening that can affect the individual’s ability to participate or perform their task (Center, n.d.).